Frequency and management of abdominal aortic aneurysms at the Hospital Universitario del Valle (1971-1980) (Colombia Medica, 1986)
The experience at the Hospital Universitario del Valle is here reported over a 10-year period with abdominal aortic aneurysm surgery; 117 patients were seen during that period, 90 male (77%) and 27 female (23%) with a mean age of 64.5 years.Symptoms included abdominal pain (75%), pulsatile abdominal mass (40%), and shock (6%). The diagnosis was mainly clinical. Although highly sensitive, paraclinical methods such as echography, cat scanning, and angiography are not considered mandatory.Forty cases were excluded from operation due to a variety of reasons, which included poor general condition due to associated diseases (28%), sudden deaths (26%), unavailable data (26%), and refusal from surgery (10%). 77 cases were operated on: 36 (47%) electively and 23 (30%) as an emergency.Mortality rates differ from whether the aneurysms were done selectively, 8.3% or ruptured, 60% data that go along with most vascular centers.From the experience at the Hospital Universitario del Valle, we recommend an aggressive approach with urgent resection and grafting as the only means for survival and prolonging life.